Activity of the banking services market in Ukraine taking into account foreign experience - Корнєєв, Юрій Валентинович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article examines the current state of the banking services market in Ukraine; the tasks are to find ways to activate lending to the real sector of the economy; concerning these tasks, the creation of new and accessible banking services for enterprises of priority and socially important sectors of the economy is defined; considered innovations that are applied in foreign banks and can be used in banking activities of Ukraine.